Sumber Daya Pendukung Pelaksanaan Kurikulum Untuk Anak Berkebutuhan Khusus di Sekolah Inklusi - Tyas, Qonitah Cahyaning; Marno, Marno (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
Children with special needs need more attention in education, because they also have potential within themselves. Parents, teachers and the government are resources that are expected to support the implementation of the curriculum for children with special needs. This research seeks to explore the role of parents, schools and government in implementing the curriculum for children with special needs, as well as any weaknesses in its implementation. Data was obtained from resource room observations, interviews with school principals and special support teachers and documentation. The results of the research show that parents, schools and the government have supported the implementation of the curriculum for children with special needs well, although there are several weaknesses in its implementation. From these results it can be concluded that parents and schools play an active role in implementing the curriculum for children with special needs, while the government is still not optimal for several reasons. Therefore, government policies must be properly enforced in their implementation.